CD19-immunoPET for noninvasive visualization of CD19 expression in B-cell lymphoma patients - Dominik Sonanini; Johannes Schwenck; Simone Blaess; Julia Schmitt; Andreas Maurer; Walter Ehrlichmann; Malte Ritter; Julia Skokowa; Manfred Kneilling; Gundram Jung; Falko Fend; Simon Krost; et al. (BMC, 2024)
Abstract Cell- and antibody-based CD19-directed therapies have demonstrated great potential for treating B-cell non-Hodgkin lymphoma (B-NHL). However, all these approaches suffer from limited response rates and considerable toxicity. Until now, therapy decisions have been routinely based on histopathological CD19 staining of a single lesion at initial diagnosis or relapse, disregarding heterogeneity and temporal alterations in antigen expression. To visualize in vivo CD19 expression noninvasively, we radiolabeled anti-human CD19 monoclonal antibodies with copper-64 (64Cu-αCD19) for positron emission tomography (CD19-immunoPET). 64Cu-αCD19 specifically bound to subcutaneous Daudi xenograft mouse models in vivo. Importantly, 64Cu-αCD19 did not affect the anti-lymphoma cytotoxicity of CD19 CAR-T cells in vitro. Following our preclinical validation, 64Cu-αCD19 was injected into four patients with follicular lymphoma, diffuse large B-cell lymphoma or mantle zone lymphoma. We observed varying 64Cu-αCD19 PET uptake patterns at different lymphoma sites, both within and among patients, correlating with ex vivo immunohistochemical CD19 expression. Moreover, one patient exhibited enhanced uptake in the spleen compared to that in patients with prior B-cell-depleting therapy, indicating that 64Cu-αCD19 is applicable for identifying B-cell-rich organs. In conclusion, we demonstrated the specific targeting and visualization of CD19+ B-NHL in mice and humans by CD19-immunoPET. The intra- and interindividual heterogeneous 64Cu-αCD19 uptake patterns of lymphoma lesions indicate variability in CD19 expression, suggesting the potential of CD19-immunoPET as a novel tool to guide CD19-directed therapies.